2011
DOI: 10.1063/1.3663863
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent optical properties of pentacene films on zinc oxide

Abstract: The optical transitions of pentacene films deposited on ZnO have been studied by absorption spectroscopy as a function of temperature in the range of room temperature down to 10 K. The pentacene films were prepared with thicknesses of 10 nm, 20 nm, and 100 nm on the ZnO-O(000-1) surface by molecular beam deposition. A unique temperature dependence has been observed for the two Davydov components of the excitons for different film thicknesses. At room temperature, the energetic positions of the respective absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 21 publications
6
38
0
Order By: Relevance
“…For the larger acenes, singlet energies change by at most 0.15 eV, while triplet energies change by even less, when varying the volume by ∼3% (similar to thermal expansion at room temperature). This agrees with the experimentally observed absence of significant temperature dependence of low-lying excitation energies [152,153].…”
Section: E Effects Of Structure On Charged and Neutral Excitationssupporting
confidence: 81%
“…For the larger acenes, singlet energies change by at most 0.15 eV, while triplet energies change by even less, when varying the volume by ∼3% (similar to thermal expansion at room temperature). This agrees with the experimentally observed absence of significant temperature dependence of low-lying excitation energies [152,153].…”
Section: E Effects Of Structure On Charged and Neutral Excitationssupporting
confidence: 81%
“…For the 7-ML-thick film, ε 2 exhibits the same spectral characteristics as for the first monolayer but is redshifted to lower energies. Actually, the ε 2 of the 7-ML-thick film closely matches the spectrum of bulk pentacene condensed in the thin-film phase [22][23][24]. Due to the resonant intermolecular interaction and the existence of two translationally nonequivalent molecules in the unit cell, the lowest electronic transition splits into two bands in the crystal due to the so-called Davydov splitting [10].…”
Section: A Evolution Of the Optical Properties During Growthmentioning
confidence: 80%
“…In fact, an increase of the Davydov splitting of pentacene thin films due to thermal contraction at low temperature has been reported by Faltermeier et al [22]. In a recent study, Helzel et al have revealed a change of the Davydov splitting of the interfacial pentacene layer due to the strain induced by the ZnO substrate at low temperature [23]. The distinct optical properties for the first monolayer can thus be attributed to the presence of the interface.…”
Section: A Evolution Of the Optical Properties During Growthmentioning
confidence: 83%
See 1 more Smart Citation
“… UV/Vis spectra of pentacene, 9 , and 14 in CH 2 Cl 2 (50 μ M ) and for solid films evaporated onto KCl substrates. For comparison, data are also shown for PEN dissolved in CH 2 Cl 2 18a and for crystalline films grown on ZnO (0001) 18b…”
Section: Resultsmentioning
confidence: 99%